PEMBELAJARAN DARING MATA PELAJARAN GEOGRAFI PADA MASA PANDEMI COVID-19 KELAS XI IIS 3 SMAN 2 SUNGAI KAKAP - Prayetno Prayetno; Nuraini Asriati; Agus Sugiarto (Universitas Tanjungpura, 2022)
This study aims to determine the process of online learning geography subjects during the Covid-19 pandemic at SMAN 2 Sungai Kakap, especially in Class XI IIS 3. The online learning carried out at SMAN 2 Sungai Kakap is the impact of the Covid-19 pandemic. The Covid-19 pandemic effected the learning process to be done by online with the aim of preventing the transmission of Covid-19. This study uses a descriptive qualitative approach. Qualitative descriptive approach was used to know and explain the facts about the online learning process of geography subjects during the Covid-19 pandemic at SMAN 2 Sungai Kakap, especially in Class XI IIS 3. The results of this study indicate the approriateness of the learning process undertaken, in particular during process of preparation, implementation and evaluation. In every completed process, it has fulfilled the online learning aspects in the form of hardware, software, and brainware. Apart from fulfilling the aspects of online learning, there are some technical problems related to network disturbances.